1999
DOI: 10.1542/peds.103.3.546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies of Families With Hearing Loss Attributable to Mutations in the Connexin 26 Gene (GJB2/DFNB1)

Abstract: Newborns with confirmed hearing loss should have Cx26 testing. Cx26 testing will help define a group in which approximately 60% will have profound or severe-profound hearing loss and require aggressive language intervention (many of these patients will be candidates for cochlear implants).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
153
6
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(178 citation statements)
references
References 14 publications
12
153
6
7
Order By: Relevance
“…In patients who were homozygous or heterozygous for 35delG, the moderate-severe degrees of hearing loss were predominant, a pattern that is in agreement with the literature 17,38,39 . Patients who are homozygous for 35delG display a large variability in the degrees of hearing loss.…”
Section: Ic -Index Cases; Hl -Hearing Losssupporting
confidence: 90%
See 1 more Smart Citation
“…In patients who were homozygous or heterozygous for 35delG, the moderate-severe degrees of hearing loss were predominant, a pattern that is in agreement with the literature 17,38,39 . Patients who are homozygous for 35delG display a large variability in the degrees of hearing loss.…”
Section: Ic -Index Cases; Hl -Hearing Losssupporting
confidence: 90%
“…As protein Cx26 is involved in the ion homeostasis of the inner ear, some of these patients may be capable of hearing, for they present a moderate hearing loss, suggesting the existence of alternative or compensatory homeostatic mechanisms. Alterations in protein Cx26 can adversely affect the development of the hearing system, resulting in variations of the degree of hearing loss or assymmetry 38 . Environmental influences, such as noises and ototoxic drugs, can be additive or synergists to the defects caused by mutations in the GJB2 gene, thus increasing the hearing loss 17,38,41 .…”
Section: Ic -Index Cases; Hl -Hearing Lossmentioning
confidence: 99%
“…The 35delG mutation is the most common mutation of GJB2 within this ethnic group [Denoyelle et al, 1997; Zelante Estivill et al, 1998]. Individuals with GJB2-related hearing loss are not at increased risk of additional health problems such as vision difficulties and mental retardation [Cohn et al, 1999]. Recent studies have suggested that infants with GJB2-related hearing loss might benefit from early cochlear implantation [Green et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…To date, 79 loci for nonsyndromic hearing loss have been identified: 40 autosomal dominant, 34 autosomal recessive, and 5 X-linked [Hereditary Hearing Loss Homepage, 2003]. Multiple studies have shown that mutations in the single GJB2 gene may account for up to 50% of nonsyndromic sensorineural autosomal recessive hearing loss or 20% of all childhood hearing loss [Denoyelle et al, 1997;Zelante et al, 1997;Cohn et al, 1999;Green et al, 2002]. The GJB2 gene encodes the connexin 26 protein, which is involved in gap junction formation allowing cell-to-cell diffusion and the transfer of ions between neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that genetic testing to determine the cause of deafness facilitates prediction of the course of hearing loss and prognostication of language development. There is, however, some controversy regarding genotype/phenotype correlation (Cohn et al 1999;Cryns et al 2004;Denoyelle et al 1999;Estivill et al 1998;Murgia et al 1999;Orzan et al 1999). For example, prediction of the degree of hearing loss was difficult, and environmental factors as well as modifier genes may have been involved (Cohn et al 1999;Murgia et al 1999;Orzan et al 1999).…”
Section: Introductionmentioning
confidence: 99%